POLITICAL COMMUNICATION: CASE STUDY OF THE STRATEGY OF CHOOSING SOCIAL MEDIA TWITTERS AS AN INSTRUMENT OF POLITICAL COMMUNICATION FOR THE 2024 PRESIDENTIAL ELECTION - Yasin, Rahman (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2025)
Social media has an important and strategic role in building public opinion, even in certain conditions, social media becomes one of the determining forces of voters' preferences. The socio-political construction played by social media in the era of digital democracy is able to change the political choices of citizens in a short time. Temporary truth is played by social media because the community is faced with various information facilities and without delving more seriously into a news report. At the presidential election campaign stage, the propaganda of the campaign team and actors using social media is very massive, including personal social media instruments such as Twitter, Facebook, YouTube, Instagram, and TikTok. The political communication instrument using Twitter social media by AMIN is one of the strategies in building positive propaganda opinions that are commonly used by other candidate pairs. This propaganda concept is considered effective for use in implementing the 2024 Presidential Election campaign stage. Propaganda has effective power to gain public sympathy. It seems that the propaganda concept approach is important because by moving this propaganda theory in an educational way, it can change public perception. The use of propaganda theory, which is an important part of political communication, determines the attitude of public preferences. The AMIN candidate pair is well aware that this propaganda approach can change a person's choice of attitude. So Twitter was chosen as one way to socialize and convey to the public about AMIN's vision and mission.